A Targeted Genetic Modifier Screen Links the SWI2/SNF2 Protein Domino to Growth and Autophagy Genes in Drosophila melanogaster. - Kwon, M.H.; Callaway, H.; Zhong, J.; Yedvobnick, B. (G3 : genes - genomes - genetics, 2013)
Targeted genetic studies can facilitate phenotypic analyses and provide important insights into development and other complex processes. The SWI2/SNF2 DNA-dependent ATPase Domino (Dom) of Drosophila melanogaster, a component of the Tip60 acetyltransferase complex, has been associated with a wide spectrum of cellular processes at multiple developmental stages. These include hematopoiesis, cell proliferation, homeotic gene regulation, histone exchange during DNA repair, and Notch signaling. To explore the wider gene network associated with Dom action, we used RNAi directed against domino (dom) to mediate loss-of-function at the wing margin, a tissue that is readily scored for phenotypic changes. Dom RNAi driven through GAL4-UAS elicited dominant wing nicking that responded phenotypically to the dose of dom and other loci known to function with dom. We screened for phenotypic modifiers of this wing phenotype among 2500 transpositions of the EP P element and found both enhancers and suppressors. Several classes of modifier were obtained, including those encoding transcription factors, RNA regulatory proteins, and factors that regulate cell growth, proliferation and autophagy, a lysosomal degradation pathway that affects cell growth under conditions of starvation and stress. Our analysis is consistent with prior studies, suggesting that Dom acts pleiotropically as a positive effector of Notch signaling and a repressor of proliferation. This genetic system should facilitate screens for additional loci associated with Dom function, and complement biochemical approaches to their regulatory activity.